Carvacrol and Thymol Hybrids: Potential Anticancer and Antibacterial Therapeutics - Sijongesonke Peter; Namhla Sotondoshe; Blessing A. Aderibigbe (Molecules, 2024)
Cancer is ranked among lethal diseases globally, and the increasing number of cancer cases and deaths results from limited access to effective therapeutics. The use of plant-based medicine has been gaining interest from several researchers. Carvacrol and its isomeric compound, thymol, are plant-based extracts that possess several biological activities, such as antimalarial, anticancer, antifungal, and antibacterial. However, their efficacy is compromised by their poor bioavailability. Thus, medicinal scientists have explored the synthesis of hybrid compounds containing their pharmacophores to enhance their therapeutic efficacy and improve their bioavailability. Hence, this review is a comprehensive report on hybrid compounds containing carvacrol and its isomer, thymol, with potent anticancer and antibacterial agents reported between 2020 and 2024. Furthermore, their structural activity relationship (SAR) and recommended future strategies to further enhance their therapeutic effects will be discussed.